2005
DOI: 10.1080/00014788.2005.9729670
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the measurement of graph distortion in financial reports

Abstract: The Graph Discrepancy Index (GDI), which originates from the lie factor introduced by Tufte (1983).is the mechanism commonly used in the financial graphics literature to determine whether graphs are distorted and to quantify the extent of such distortion. Although the GDI is critical to the financial graphics literature, little or no attention has been paid to its robustness and accuracy. We critically examine the mathematical characteristics of the GDI and show its limitations as a measure of graph distortion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 15 publications
1
36
0
2
Order By: Relevance
“…They show that measurement distortion in excess of 10% is just perceptible to users. Since 1992, there have been a succession of financial graphics studies (e.g., Beattie andJones, 2000 and2001;Courtis, 1997;Frownfelter-Lohrke and Fulkerson, 2001;Mather, Ramsay and Serry, 1996;Mather, Ramsay and Steen, 2000;and Mather, Mather and Ramsay, 2005) all of which have developed, and reinforced, the earlier findings of selectivity, measurement distortion and presentational enhancement.…”
Section: Financial Graphs In Annual Reportsmentioning
confidence: 99%
“…They show that measurement distortion in excess of 10% is just perceptible to users. Since 1992, there have been a succession of financial graphics studies (e.g., Beattie andJones, 2000 and2001;Courtis, 1997;Frownfelter-Lohrke and Fulkerson, 2001;Mather, Ramsay and Serry, 1996;Mather, Ramsay and Steen, 2000;and Mather, Mather and Ramsay, 2005) all of which have developed, and reinforced, the earlier findings of selectivity, measurement distortion and presentational enhancement.…”
Section: Financial Graphs In Annual Reportsmentioning
confidence: 99%
“…In this case the GDI would require you to divide by zero, which is not possible. Mather et al (2005) have found a possible solution to overcome this problem with their Relative Graph Discrepancy index (RGD). Even though this measure produces stronger results, their conclusions are only based on one research.…”
Section: Limitationsmentioning
confidence: 99%
“…After all, a favourable distortion of graphs changes users' perception of the charity's performance (Beattie and Jones, 1994;Mather et al, 2005) and affects judgement and decisions (Xu, 2005), e.g. of donors.…”
Section: Research Topicsmentioning
confidence: 99%
“…Second, we investigated via t-tests whether during the global financial crisis: unfavourable cross-sectional comparisons were equal or higher than favourable (Hypothesis 3a); time-series portraying a declining trend were equal or higher than those with a rising trend (Hypothesis 3b); and stock market performance graphs which included other bank's indicators portraying a negative performance were equal or higher than those portraying a positive performance (Hypothesis 3c). To test impression management by commission via measurement distortion (Hypothesis 2b), we considered both mandatory and voluntary graphs, but excluded 12 graphs because RGD values were undefined and 5 because the RGD could not be calculated (Mather et al, 2005).…”
Section: Contextualisations As Measures Of Retrospective Sense-makingmentioning
confidence: 99%
“…We considered a cut-off level of +/-2.5% to distinguish between material and non-material distortions (Falschlunger et al, 2015;Mather et al, 2005;Muiño & Trombetta, 2009). Positive and negative values of RGD represent favourable and unfavourable distortions, respectively (Mather et al, 2005). Favourable (unfavourable) distortions overstate (understate) increasing trends or understate (overstate) declining trends.…”
Section: Favourable Measurement Distortion and Cross-sectional Performentioning
confidence: 99%